Staged invasions across disparate grasslands: effects of seed provenance, consumers and disturbance on productivity and species richness. (28th January 2014) - Maron, John L.; Auge, Harald; Pearson, Dean E.; Korell, Lotte; Hensen, Isabell; Suding, Katharine N.; Stein, Claudia; Chase, Jonathan
Abstract Exotic plant invasions are thought to alter productivity and species richness, yet these patterns are typically correlative. Few studies have experimentally invaded sites and asked how addition of novel species influences ecosystem function and community structure and examined the role of competitors and/or consumers in mediating these patterns. We invaded disturbed and undisturbed subplots in and out of rodent exclosures with seeds of native or exotic species in grasslands in Montana, California and Germany. Seed addition enhanced aboveground biomass and species richness compared with no‐seeds‐added controls, with exotics having disproportionate effects on productivity compared with natives. Disturbance enhanced the effects of seed addition on productivity and species richness, whereas rodents reduced productivity, but only in Germany and California. Our results demonstrate that experimental introduction of novel species can alter ecosystem function and community structure, but that local filters such as competition and herbivory influence the magnitude of these impacts.